2014
DOI: 10.1007/s10853-014-8524-5
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally controlled emulsion electrospinning for the encapsulation of temperature-sensitive compounds

Abstract: The introduction of highly volatile fragrances within polymeric nano-scaled fibers is a promising route for efficient and simple encapsulation of temperature-sensitive materials. This work describes the investigation of selected parameters influencing the electrospinning of emulsions of poly(vinyl alcohol) (PVA) and (R)-(?) limonene or hexadecane. Thereby the influence of environmental parameters such as temperature and relative humidity on the fiber structure and encapsulation efficiency (EE) of the fragrance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The relative humidity has been reported before to possess a strong influence on fiber formation from PVA and other water soluble polymers with lower values resulting in faster evaporation and thereby thicker fibers. [38][39][40][41] As expected, we found generally homogeneous but slightly thicker fibers at lower relative humidity to yield a lower amount of elongated ESPs (Fig. 2C), a result which can be attributed to the strong relationship between fiber diameter and cluster elongation.…”
Section: Detailed Work Procedures and Process Optimizationsupporting
confidence: 70%
“…The relative humidity has been reported before to possess a strong influence on fiber formation from PVA and other water soluble polymers with lower values resulting in faster evaporation and thereby thicker fibers. [38][39][40][41] As expected, we found generally homogeneous but slightly thicker fibers at lower relative humidity to yield a lower amount of elongated ESPs (Fig. 2C), a result which can be attributed to the strong relationship between fiber diameter and cluster elongation.…”
Section: Detailed Work Procedures and Process Optimizationsupporting
confidence: 70%
“…Emulsion electrospinning enables the encapsulation of compounds within fibers for drug delivery applications and fabrication of porous fibers to enhance mesh porosity. Many studies have reported successful encapsulation of hydrophobic compounds (mineral oil, β‐carotene, fish oil, and n ‐butyl acetate) within hydrophilic polymers . Surfactants such as Pluronics P105, Tween 20, and Span 80 are often used to stabilize the emulsion for the course of spinning.…”
Section: Electrospinning Modificationsmentioning
confidence: 99%
“…Many studies have reported successful encapsulation of hydrophobic compounds (mineral oil, b-carotene, fish oil, and n-butyl acetate) within hydrophilic polymers. [65][66][67][68][69] Surfactants such as Pluronics P105, Tween 20, and Span 80 are often used to stabilize the emulsion for the course of spinning. Enzymes, growth factors, and drugs are often emulsified within hydrophobic polymers to retain bioactivity and promote sustained release over standard blending procedures.…”
Section: Effects Of Modulating Solution and Processing Parametersmentioning
confidence: 99%
“…It was selected to be encapsulated in bers fabricated by the electrospinning of emulsions of poly(vinyl alcohol) (PVA). 57 In this study, the effects of two environmental parameters including temperature (8 to 24 C) and relative humidity (55 to 85%) on the formation of bers were investigated. Hexadecane, with low volatility and high melting point, was applied as the dispersed phase.…”
Section: Food Applicationsmentioning
confidence: 99%